Multi-hop Clock Synchronization in Wireless Ad-Hoc Networks - Christmann, Dennis; Gotzhein, Reinhard; Kuhn, Thomas (Electronic Communications of the EASST, 2009)
In this paper, we introduce Black Burst Clock Synchronization (BBCS), a novel protocol for multi-hop time synchronization in wireless ad-hoc networks, located at MAC level. BBCS is based on the exchange of synchronized tick and time frames, which are protected against collisions by a special encoding using black bursts. It provides a deterministic upper bound for clock offset that only depends on maximum network diameter, and on the used transceiver hardware. BBCS has low complexity in terms of communication, computation, storage, structure, and energy consumption. It provides low and deterministic convergence delay, and is robust against node movements and node failures. In this work, we introduce BBCS, provide a formal analysis of its properties, and evaluate the required overhead for clock-synchronizing a multi-hop wireless ad-hoc network.